2021
DOI: 10.3389/fpsyg.2021.679476
|View full text |Cite
|
Sign up to set email alerts
|

Are Soccer and Futsal Affected by the Relative Age Effect? The Portuguese Football Association Case

Abstract: A better understanding of the relative age effect (RAE) in youth will increase the awareness of the need for reducing the bias of (de)selection. Thus, we investigated the RAE in youth female and male soccer and futsal players in Portugal, using nationwide data. Birthdates of 5,306 female and 126,285 male soccer players, and 2,437 female and 23,988 male futsal players (U7–U19), registered in Portugal during the season 2019–2020, and Portuguese National teams (from U15 to AA soccer teams and from U17 to AA futsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 36 publications
5
31
0
1
Order By: Relevance
“…In a male context, the magnitude of RAE is well documented, especially in sports where physical factors are fundamental for success [ 1 ] affecting a wide range of individual [ 6 , 11 , 12 , 15 ] and team sports from childhood to adulthood [ 14 , 16 , 17 , 18 , 19 , 20 ]. However, RAE may be influenced by sex differences.…”
Section: Introductionmentioning
confidence: 99%
“…In a male context, the magnitude of RAE is well documented, especially in sports where physical factors are fundamental for success [ 1 ] affecting a wide range of individual [ 6 , 11 , 12 , 15 ] and team sports from childhood to adulthood [ 14 , 16 , 17 , 18 , 19 , 20 ]. However, RAE may be influenced by sex differences.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies have been reported when seeking to understand the RAE in physical demands (Hill et al, 2020;Patel et al, 2020;Figueiredo et al, 2021). Patel et al (2020) reported that somatic maturity and anthropometric and physical performance characteristics distinguished retained or dropout individuals in an age group-dependent manner as opposed to birth quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Joyner et al 14 suggest that the advantage generated during the selection and identification phases seems to disappear over time and may even be reversed in the transition to the elite sport. Indeed, the reduction of RAE as chronological age advances has been observed for several team sports in their respective countries 12,13 . Since the criteria for identifying talents and for the progressive development of the athlete may depend on the national or local culture and/or sports philosophy 15 , it is important to assess whether this relationship between age category and prevalence of RAE also occurs with sports of lesser popularity, as is the case of water polo in Brazil.…”
Section: Introductionmentioning
confidence: 95%
“…The constraints-based model 10 proposes that RAE existence and/ or dimension in the sports context is a consequence of the interaction of individual, environment, and task constraints. Regarding the individual's factors, the phase of the sports career seems to be a factor related to the existence of the RAE, since the magnitude of this effect tends to decrease as chronological age advances 11,12 . Bezuglov et al 13 showed that elite Russian soccer athletes from senior teams exhibited a less pronounced RAE compared to youth teams.…”
Section: Introductionmentioning
confidence: 99%